Kajian Preferensi Masyarakat dan Sikap Pemerintah Terkait Reaktivasi (Penghidupan Kembali) Jalur Kereta Api Semarang - Yogyakarta - Reinaldo Butar Butar (Jurnal Wilayah dan Lingkungan, 2015)
Connected with a road line of ± 130 km length, the human traffic along Semarang – Magelang – Yogyakarta corridor heavily depends on road transportation modes. This creates traffic congestions on particular road strips of Bawen – Ambarawa – Magelang – Yogyakarta. Currently, the government plans to exercise a policy to reactivate the dead railroad between Semarang and Yogyakarta. Once being implemented, it may provide people an alternative choice of transportation mode. The study aimed to assess people's preference and attitude toward the policy. This study was conducted using a mixture of qualitative and quantitative research. Descriptive quantitative and qualitative methods were used through scoring analysis of the people’s preference, cross tabulation analysis, and qualitative descriptive analysis. The findings revealed that variables of travel cost, travel time, accessibility, and qualitative attitude (comfort, security, and safety) have relations to their preference for the modal switch. Compared to the government attitude, there are only qualitative attitude and accessibility variables which are similar. In terms of travel cost and travel time variables, they actually do not conform each other.